Penerapan Pembelajaran Sains melalui Inkuiri pada Anak Usia Dini - Elva M. Sumirat; Sartika K. Ismail; Nur Indah Dg Mareto; Mukmin Kadoli Umar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the application of the inquiry approach in science learning for early childhood. The inquiry approach is believed to be able to foster curiosity, critical thinking skills, and exploration skills in children from an early age. The research method used is descriptive qualitative with observation and documentation techniques. The subjects of the study were children in the Playgroup at Kiddie Care. The results of the study indicate that the inquiry approach can increase children's active involvement in the science learning process, such as when observing objects, asking questions, and trying to find answers through simple experiments. The application of inquiry also encourages children's communication and cooperation skills in groups. Thus, the inquiry approach is effectively applied in science learning in PAUD.